PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS DISCOVERY LEARNING MELALUI E-LEARNING PADA MATERI EKOSISTEM - Fatikhatun Nikmatus Sholihah; Lia Ati'ur Rosyidah (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2021)
This study aims to develop a learning device Discovery Learning on the subject matter Ecosystem Class X MAN 4 Jombang. The products developed in this research are Syllabus, RPP and LKPD E-Learning. This study uses the Research and Development (R&D) method. The feasibility instruments used in this study are in the form of a material validation questionnaire and a media or learning device validation questionnaire. The research results obtained are: (1). The Discovery Learning learning device was declared feasible with a lesson plan value of 77 by the material expert validator, 65 by the learning device expert validator (2). Student worksheets (LKPD were declared very feasible with a score of 82 by the material expert validator, 76 by the learning device expert validator. (3) The question assessment instrument was declared very feasible by the material expert validator with a score of 82, while the learning device expert validator gave a score of 82. 62 with decent category.